Pemanfaatan Media Sosial dalam Melakukan Jual Beli Online melalui Instagram - Harmelia; Devi Edriani (Jurnal Teknologi, 2021)
This study analyzes the use of sosial media in buying and selling online through Instagram (case study: UPI YPTK Padang student). The development of online shops or online shops through internet media has been very much in Indonesia. Online shops offer various facilities that can be accessed by people who understand technology, so that traditional sales have begun to shift in function because many online shops sell by utilizing sosial media such as Instagram. This study uses descriptive qualitative research methods. The population in this study were students of the Faculty of Economics UPI YPTK Padang in 2020. The sampling technique was purposive random sampling with a sample size of 200 people. Data retrieval in this study was by distributing questionnaires to students using google forms and media chat which was carried out using the whats app application. From the data obtained, it is known that the use of sosial media for online buying and selling among students has a fairly high level of respondent achievement, which is 79%. while for the use of sosial media for online buying and selling based on the gender of the respondents, only 33% were used by students, while 66% were used by students and for. The reason respondents use Instagram to shop online is that 43% agree that buying and selling online makes it easy to access because it can be done anywhere and anytime.